Ionic Covalent Organic Frameworks‐Derived Cobalt Single Atoms and Nanoparticles for Efficient Oxygen Electrocatalysis. Issue 2 (30th December 2022) - Guo, Jiaming; Li, Wenqiong; Xu, Yuncun; Mao, Yanqi; Mei, Zhiwei; Li, Haihan; He, Yun; San, Xingyuan; Xu, Kui; Liang, Xiaoguang
Abstract: Metal single atoms show outstanding electrocatalytic activity owing to the abundant atomic reactive sites and superior stability. However, the preparation of single atoms suffers from inexorable metal aggregation which is harmful to electrocatalytic activity. Here, ionic covalent organic frameworks (iCOFs) are employed as the sacrificial precursor to mitigate the metal aggregation and subsequent formation of bulky particles. Molecular dynamics simulation shows that iCOFs can trap and confine more Co ions as compared to neutral COFs, resulting in the formation of a catalyst composed of Co single atoms and uniformly distributed Co nanoparticles (CoSA &CoNP‐10 ). However, the neutral COFs derive a catalyst composed of Co atomic clusters and large Co nanoparticles (CoAC &CoNP‐25 ). The CoSA &CoNP‐10 catalyst exhibits higher oxygen bifunctional electrocatalytic activities than CoAC &CoNP‐25, coinciding with the density functional theory results. Taking the CoSA &CoNP‐10 as the air cathode in Zn–air batteries (ZABs), the aqueous ZAB presents a high power density of 181 mW cm −2, a specific capacity of 811 mAh g −1 as well as a long cycle life of 407 h at a current density of 10 mA cm −2, while the quasi‐solid state ZAB displays a power density of 179 mW cm −2 and the cycle life of 30 h. Abstract : Ionic covalent organic frameworks (iCOFs)‐derived catalysts composed of Co single atoms and Co nanoparticles are prepared. Molecular dynamics simulation presents the ion exchange process for the preparation of iCOFs‐Co precursor. The catalyst exhibits superior electrocatalytic activities due to the interactions betweenCo single atoms and nanoparticles. Taking the catalysts as air cathodes, the assembled Zn–air batteries display high performances.